KEMİK MİNERAL YOĞUNLUĞU ÖLÇÜMLERİNE 99mTc TÜM VÜCUT KEMİK AKTİVİTESİNİN ETKİLERİ - DEMİR, Mustafa; ÖZMEN, Özlem; USLU, İlhami (Cerrahpaşa Medical Journal, 2019)
Background and Design.- The object of this study is to investigate the effect on bone mineral density (BMD) / bone marrow for the patients who were referred for whole body scanning by 99mrc on the same day. We studied the bone density of the patients before and after whole body scintigraphy on the same day. Results.- Before studying the patients, we calculated the standard counts of bone mineral density using DEXA phantom within L1-4 vertebra. We made a point source and a flat phantom with 99mrc. When using these sources along with DEXA phantom, we calculated BMD at different activities; e.g. 92.5, 185, 370 MBq. We selected 17 patients visiting our Nuclear Medicine department, irrespective of sex and age limits. Conclusion.- In phantom study, there was no change in BMD in the presence of radionuclide 99mrc. Normally the clinical uses of radioactive materials do not make any significant effect on BMD. From our study, we also did not find any significant change in BMD of the patients after a whole body bone scintigraphy.